Does Tax Morale Able to Moderate the Relationship Between Perceptions of Corruption and Taxpayer Compliance? - Subhan Subhan; Ustman Ustman; Fahorrahman Fahorrahman (Jurnal Akademi Akuntansi, 2023)
Purpose: The purpose of this research is to examine the effect of perceptions of corruption on taxpayer compliance with tax morale as a moderating variable. Methodology/approach: This research is explanatory research. The population in this study amounted to 29.555 Individual Employee Taxpayers. The sampling technique used the slovin method, so the research sample amounted to 100. The data collection technique uses a questionnaire by distributing questionnaires and google forms. The number of questionnaires used in the analysis was 100 questionnaires (100%). Analysis of the data in this study using Moderated Regression Analysis (MRA). Findings: Research results show that tax morale can moderate the relationship between Corruption Perceptions and Taxpayer Compliance, thus high corruption is influenced by low levels of morality and ultimately also has an impact on taxpayer compliance, so as to minimize corruption levels high morale is required. Practical and Theoretical contribution/Originality: The results of this study confirm the theoretical study of perceptions of corruption on taxpayer compliance by moderating tax morale so that it can be used as a reference for academics. For Fiscus, it can contribute ideas on how tax morale can be increased to reduce public perceptions of corruption so that taxpayer trust and compliance will also increase.